Characterization of native strains of Azospirillum spp. and its effect on growth of Oryza sativa L. “rice” in Lambayeque - García, Franklin (2010)
This research was conducted to characterize and determine the effect of native strains of Azospirillum spp. on growth of Oryza sativa L. "rice" as an alternative for the reduction of chemical fertilizers. The bacteria were isolated from roots of rice in Lambayeque. Fragments of previously disinfected roots were planted in Nfb semisolid medium, were nitrogen-fixing bacteria were recognized by a whitish film on the surface and turn from green to blue. The genus Azospirillum was identified in Congo red agar medium, obtained 96 isolates with production of 2.69 to 38.02 ppm indoleacetic acid and 7.95 to 29.09 ppm of fixed nitrogen. The four strains with the highest values were inoculated independently and in combination with 50 and 100 % urea in Tinajones INIA508 rice. It used a completely randomized design and including witnesses’ 50 and 100 % urea and absolute control. All native strains increased height and dry matter of shoot and roots, with effectiveness index of up to 21.77, 102.06 and 126.11 % compared to untreated control. Azospirillum sp. GM-86 selected by the highest value of indoleacetic acid, reached the highest level of effectiveness in height and root dry biomass. The application of 50 % úrea with Azospirillum spp. increased rates of effectiveness. It demonstrated the potential of native strains of Azospirillum spp. to increase the growth of rice as well as the possibility to use associate with low doses of urea.